A review of early severe weather applications of high‐resolution regional reanalysis in Australia. (17th August 2022) - Fox‐Hughes, Paul; Su, Chun‐Hsu; Eizenberg, Nathan; White, Christopher; Steinle, Peter; Jakob, Doerte; Black, Mitchell; Dowdy, Andrew; Brown, Andrew; Nathan, Rory; Acharya, Suwash Chandra
Abstract: High‐resolution regional reanalysis datasets have the potential to provide valuable guidance to emergency management agencies, highlighting areas at risk of severe weather, including estimates of return periods of various hazardous weather phenomena. The BARRA regional reanalysis for Australia comprises a reanalysis for a broad region around Australia at moderately high spatial and temporal resolution (12 km/hourly), together with four subdomains at high resolution (1.5 km/1 h). Here, we document four applications of BARRA developed for emergency management: optimal placement of portable automatic weather stations for fire weather monitoring; climatology of low‐level wind shear conducive to cool‐season tornadogenesis; development of rainfall intensity–frequency–duration curves based on the gridded reanalysis data; and development of a climatology across Australia of parameters associated with severe thunderstorm occurrence. Abstract : We document several applications of the Australian Bureau of Meteorology Atmospheric high‐resolution Regional Reanalysis for Australia (BARRA), including for very high resolution subdomains illustrated in the accompanying figure. The applications are focussed on emergency management problems, given their high priority and the strong early support of emergency management agencies in the development of BARRA.